2009
DOI: 10.1016/j.microrel.2009.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental verification of the impact of negative bias temperature instability on CMOS inverter

Abstract: The effects of negative bias temperature instability (NBTI) on the performance of a CMOS inverter have been investigated by means of both simulation and experimental methods. The simulation of NBTI effects on CMOS inverter has been done by shifting the pFET V tho BSIM parameter. The results show that NBTI shifts the inverter transfer curve, reduces the low noise margin and current consumption but increases the high noise margin. A good agreement between simulation and experimental results has been obtained. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…From this graph, it shows that the VTC is shifted toward the left hand side after 10 years stress was applied and this is in agreement in a work done by N. Berbel [8]. As the threshold voltage shifts, the maximum gain point also shifts ∆V M as described in the following equation [8]: on which in rcuit delays, hich occurs ion of the (6) d V th is the , it can be e current is n of the µ FE section will e threshold Table 2 shows the maximum gain point shift; ∆V M of the VTC for the simulated inverter and it is observed that the ∆V M increases with stress time for three different temperatures.…”
Section: Voltage Transfer Characteristic (Vtc)supporting
confidence: 91%
“…From this graph, it shows that the VTC is shifted toward the left hand side after 10 years stress was applied and this is in agreement in a work done by N. Berbel [8]. As the threshold voltage shifts, the maximum gain point also shifts ∆V M as described in the following equation [8]: on which in rcuit delays, hich occurs ion of the (6) d V th is the , it can be e current is n of the µ FE section will e threshold Table 2 shows the maximum gain point shift; ∆V M of the VTC for the simulated inverter and it is observed that the ∆V M increases with stress time for three different temperatures.…”
Section: Voltage Transfer Characteristic (Vtc)supporting
confidence: 91%